SHARIA AUDIT PROBLEMS IN ZAKAT INSTITUTIONS: EVIDENCE FROM INDONESIA - As-Salafiyah, Aisyah; Rusydiana, Aam Slamet (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
This study aims to determine the opinions and recommendations from the experts regarding the problem of the audit system in zakat institutions in Indonesia to determine the priority of the most important variables to be fixed. This research was conducted in August 2020 using primary data obtained from interviews with experts consisting of academics, practitioners and regulators with a background in sharia economics. The data were analyzed by the Delphi method to find the main priority and agreed upon convergence by experts. The results showed that of the 15 variables of audit problems at zakat institutions in Indonesia, there are 13 variables with convergent-convergent consensus based on expert opinion and only 2 variables with divergent consensus. The 3 main priority problems of auditing in zakat institutions in Indonesia are (1) an Insufficient number of sharia auditors, (2) The absence of strong rules related to sharia auditing, (3) HR competence. This research can be used by readers to make improvements in the audit system of zakat institutions in Indonesia with priority according to the findings of this study. This research is the first research that comprehensively calculates the expert's assessment regarding audit problems in Indonesian zakat institutions using the Delphi method and its priority recommendations